2016
DOI: 10.1038/srep36081
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hemorrhagic fever with renal syndrome in Qingdao City, China, 2010–2014

Abstract: Hemorrhagic fever with renal syndrome (HFRS) was considered to be transmitted by Apodemus agrarius and Rattus norvegicus, the principal animal hosts of Hantaan virus and Seoul virus, respectively. The aim of this study is to determine the correlation of HFRS incidence with capture rate and hantavirus infection rate of rodent species in Qingdao City, China. We collected HFRS patients’ information and captured field and residential rodents in Qingdao City, China from 2010 to 2014. The correlations of HFRS incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 9 publications
1
21
0
Order By: Relevance
“…Previously, in the rural population of two prefecture-level cities (Zibo and Qingdao) of China, we found HFRS had a high incidence rate which ranged from 1.96 cases/100,000 persons to 28.9/100,000 in different years [10,11]. These studies indicated HFRS was epidemic in these areas.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Previously, in the rural population of two prefecture-level cities (Zibo and Qingdao) of China, we found HFRS had a high incidence rate which ranged from 1.96 cases/100,000 persons to 28.9/100,000 in different years [10,11]. These studies indicated HFRS was epidemic in these areas.…”
Section: Introductionmentioning
confidence: 78%
“…These studies indicated HFRS was epidemic in these areas. Peridomestic rodents were also captured for orthohantavirus detection in the two cities and orthohantavirus antigens were found by immunofluorescence assay in 5.2% (29/559) and 3.8% (9/240) of these rodents, respectively [10,11], and the seropositive rate to hantavirus of host animals was as high as 23.3% [12]. Hantaan orthohantavirus (HTNV) and Seoul orthohantavirus (SEOV) are the causative agents of HFRS in these areas.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies showed that the orthohantavirus seroprevalence in Asian countries, for example China, Korea, Thailand and Singapore prevailed between 0.5% and 33.3%, and in European countries between 0% and 24%. (Bi et al, ; Mertens et al, ; Jiang, Zhang, et al, ; Xiao et al, ; Zou, Chen, & Sun, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Positive Hantavirus found in R. norvegicus in the study site is higher than the number found in other studies performed in some countries in the world. The prevalence rate of hantavirus infection in R. norvegicus was reported in between 6.3% to 17.8% [11][12][13]. However, the result of study in Indonesia revealed various results.…”
Section: Discussionmentioning
confidence: 99%